PSO Based Path Planning Strategy in Manufacturing Plants with Unknown Environmental Criteria - Ramakrishna, B.; Subbaiah, K. Venkata (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In the present era, mobile robots have been widely used in industrial sectors for transferring goods/tools from one place to another with in the manufacturing plant. It is a challenging task to develop an efficient motion planner of a mobile robot, if the robot is moving in unknown environments. Hence, the current research work aims at developing an intelligent motion planning strategy using particle swarm optimization in order to transport the goods within the manufacturing plant. Finally, simulation results have been presented to validate the efficiency of the proposed algorithm.